Design and synthesis of cabotegravir derivatives bearing 1,2,3-triazole and evaluation of anti-liver cancer activity - Xie, Huaxia; Mao, Longfei; Fan, Gaolu; Wu, Ziyuan; Wang, Yimian; Hou, Xixi; Wang, Jiangang; Wang, Huili; Liu, Ling; Li, Sanqiang (Frontiers in Pharmacology, 2023)
Based on the structure of the anti-HIV drug cabotegravir, we introduced 1,2,3-triazole groups with different substituents to obtain 19 cabotegravir derivatives and tested their activity against HepG2 cells. The proliferation of HepG2 cells were examined following treatment with derivatives. Most of the compounds demonstrated significant inhibitory effects, particularly compounds KJ-5 and KJ-12 with IC 50 values 4.29±0.10 μM and 4.07±0.09 μM, respectively. Furthermore, both compounds 5 and 12 significantly caused cell apoptosis, G2/M arrest, DNA damage, and suppressed invasion and migration in a concentration-dependent manner. In addition, KJ-5 and KJ-12 could trigger apoptosis via the mitochondrial pathway by increasing the ratio of Bax/Bcl-2 and activating cleaved-caspase-9, cleaved-caspase-3, and cleaved-PARP.